Comprehensive Insights into Post-Traumatic Trigeminal Neuropathy: Pathophysiology, Diagnosis, and Management Approaches - Susanna Halim; Diana Mayleen Halim (Journal of Science and Science Education, 2026)
Post-Traumatic Trigeminal Neuropathy (PTTNP) is a debilitating orofacial pain condition resulting from trauma or surgical interventions involving the trigeminal nerve. Despite growing attention in clinical literature, diagnosis and management remain challenging. This review aims to critically examine current literature regarding the pathophysiology, clinical features, diagnostic tools, and therapeutic options related to PTTNP. Diagnosis of post-traumatic trigeminal neuropathy (PTTNP) is established through a structured clinical assessment. This includes detailed patient history, evaluation of pain characteristics and functional impairment, objective sensory testing such as Quantitative Sensory Testing (QST) and two-point discrimination, as well as adjunctive imaging modalities like MRI and DTI. Prognostic evaluation may be enhanced by predictive models that integrate subjective and objective findings. Findings emphasize the importance of early diagnosis, highlight subjective and objective sensory assessment tools, and outline both pharmacological and surgical strategies with varied outcomes. Predictive models and psychological factors are crucial in prognosis and recovery. PTTNP is a complex condition requiring interdisciplinary collaboration. Early intervention, comprehensive diagnostics, and personalized treatment plans are vital for optimal outcomes